A Golden Synthetic Approach to 2-(1H-Pyrrol-1-yl)anilines and Pyrrolo[1,2-a]quinoxalines through a Gold Carbene Intermediate - Tasdemir, Volkan; Genç, Hasan; Menges, Nurettin (Synlett, 2023)
The pyrrolo[1,2-a]quinoxaline skeleton has significant potential for many biological and optical applications. Hence, in this study, unconjugated ynone derivatives were treated with 1,2-diaminoarenes in a gold-catalyzed cyclization to give 2-(1H-pyrrol-1-yl)anilines, which are valuable starting materials, and pyrrolo[1,2-a]quinoxalines by a one-pot and single-step approach. A reaction mechanism for the formation of the pyrrolo[1,2-a]quinoxaline skeleton featuring a key gold carbene intermediate is proposed. On the other hand, the methyl group on the C-2 position of the 2-(1H-pyrrol-1-yl)anilines was oxidized by SeO2 to give the pyrrolo[1,2-a]quinoxaline skeleton, resulting in 14 different pyrrolo[1,2-a]quinoxaline derivatives.
Keywords: pyrroloquinoxalines; diaminoarenes; pyrrolylanilines; gold catalysis; cyclization; oxidation